A checklist of the current valid species of the subfamily Triatominae Jeannel, 1919 (Hemiptera, Reduviidae) and their geographical distribution, with nomenclatural and taxonomic notes - Galvão, Cleber; Carcavallo, Rodolfo; Rocha, Dayse Da Silva; Jurberg, José (Zootaxa, 2003)
A checklist of the 137 current valid species placed in the subfamily Triatominae and their geographical distribution is presented. Confirmed and doubtful synonyms are given, as are nomenclatural and taxonomic comments.